2014
DOI: 10.1371/journal.pone.0087702
|View full text |Cite
|
Sign up to set email alerts
|

Selective Alleviation of Mitomycin C Sensitivity in lexA3 Strains of Escherichia coli Demands Allele Specificity of rif-nal Mutations: A Pivotal Role for rpoB87-gyrA87 Mutations

Abstract: Very recently, we have reported about an unconventional mode of elicitation of Mitomycin C (MMC) specific resistance in lexA3 (SOS repair deficient) mutants due to a combination of Rif-Nal mutations (rpoB87-gyrA87). We have clearly shown that UvrB is mandatory for this unconventional MMC resistance in rpoB87-gyrA87-lexA3 strains and uvrB is expressed more even without DNA damage induction from its LexA dependent promoter despite the uncleavable LexA3 repressor. The rpoB87 allele is same as the rpoB3595 which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Interstrand cross-links, which are one type of DNA damage caused by MMC, are in E. coli repaired by proteins involved in the HR, NER, and TLS pathways ( Van Houten et al 1986 ; Sladek et al 1989 ; Slater and Maurer 1993 ; Berardini et al 1999 ), all of which are upregulated as part of the SOS regulon ( Radman 1975 ; Little and Mount 1982 ; Walker et al 1982 ; Friedberg et al 2005). Indeed, we observed that the impossibility of inducing the SOS response in the lexA (Ind − ) genetic background resulted in a very high sensitivity of the cells to MMC (data not shown), as previously reported ( Shanmughapriya et al 2014 ).…”
Section: Discussionsupporting
confidence: 86%
“…Interstrand cross-links, which are one type of DNA damage caused by MMC, are in E. coli repaired by proteins involved in the HR, NER, and TLS pathways ( Van Houten et al 1986 ; Sladek et al 1989 ; Slater and Maurer 1993 ; Berardini et al 1999 ), all of which are upregulated as part of the SOS regulon ( Radman 1975 ; Little and Mount 1982 ; Walker et al 1982 ; Friedberg et al 2005). Indeed, we observed that the impossibility of inducing the SOS response in the lexA (Ind − ) genetic background resulted in a very high sensitivity of the cells to MMC (data not shown), as previously reported ( Shanmughapriya et al 2014 ).…”
Section: Discussionsupporting
confidence: 86%
“…This phenotype was originally called as SOS Independent Repair (SIR) and now called as SOS Interdependent Repair. Subsequently, allele specificity of rif‐nal mutations in the elicitation of this unorthodox phenotype was also reported . Most recently we have shown that one of the characteristic phenotype of Δlon mutant viz capsule over‐expression can be suppressed by two novel rif alleles ( rpoB12 and rpoB77 ) .…”
Section: Introductionmentioning
confidence: 91%